Climatic Zoning of Khuzestan Province Based on Litten Ski Method - Seyede Lale Sadat Asl; Gholamreza Yavari; Farid Ejlali (Nīvār)
Implementing sustainable development of regions requires careful planning based on talents and resource constraints, and the climate of each region is one of the most important factors determining the development potential of the place. In this regard, climatic characteristics and its dominant elements that play a decisive role in the dispersal and formation of vital phenomena (plants, animals, humans) are considered as one of the most important natural-environmental factors. If the guarantee of complete success of most agricultural development plans, industry, irrigation projects, transportation, health, etc. is achieved when it is accompanied by knowledge of the climate and the use of its various potentials. The purpose of this study is to classify the climate of Khuzestan province based on litany-skiing method. The litany-skiing method uses the three basic elements of temperature, precipitation and coefficient. This method uses auxiliary indicators for comprehensive classification, which include three indicators of compliance, dry season duration and solar radiation status.To calculate meteorological data index including precipitation, minimum temperature, maximum temperature and relative humidity of 13 meteorological stations including Ahvaz, Izeh, Andimeshk, Mahshahr, Behbahan, Dezful, Azadegan, Ramhormoz, Shushtar, Masjed Soleiman, Omidieh, Shadegan and Shousha during 1991. Collected until 1397. Excel and SPSS software were used to calculate and analyze the indicators. The results showed that the climatic situation of Khuzestan cities was divided into 4 groups based on the coefficient of lithium ski index.